تأثير أسلوب الغناء لتنمية فهم علم الالات لدى طلاب الفصل الثاني بمعهد دار الحكمة الإسلامي فراسوغ بودوران سيدوارجو - M. Asad Nahdly; Muhammad Zamzain Al Mubaro (Al-Muttaqin : Jurnal Studi, Sosial, dan Ekonomi, 2022)
arul Hikmah Islmaic Boarding School in which the Arabic languagebecomes the language of communication for students because of what has beenmentioned that needs to understand machine science, and teachers have fallen intodifficulties in making this, because the song is one of the methods that the researcherchooses to develop understanding. Using the song makes it easier for students tounderstand. Singing is a style. The style is a set of rules or controls used in teachingmethods to achieve the goals of teaching. As it is known that life has a goal, andevery action has a goal. The general purpose of the research is: 1) To know the effectof the singing style for developing the understanding of instrumental science among students of the second semester at the Darul Hikmah Islmaic Boarding School,Prasung, Buduran Sidoarjo. 2) To find out the effect of the singing style ondeveloping the understanding of instrumental science among students of the secondsemester at the Darul Hikmah Islmaic Boarding School. As for the approach to thisresearch, it is the quantitative approach, and the type of research is experimentalresearch. And the entrance to this research is a quantitative approach and the use ofquantitative analysis, which assumes that the observed phenomena It is measured innumerical form. The method of collecting data that the researcher is conducting isthe method of testing and observation. Based on the result of the effect of the singingstyle to develop the understanding of instrumental science among students of thesecond semester at the Darul Hikmah Islmaic Boarding School, Prasung BuduranSidoarjo. The presence of the relationship and the influence on the students is: Weknow from the researcher's t-test result. The researcher knew that the statistic t of 10is greater than the tabular t, the moral level 1% means 2.80, and also greater than themoral level 5% 2.06. Thus, he knows that Ha is acceptable and Ho is rejected.Therefore, the use of singing style has a relationship and impact in developing theunderstanding of instrumental science among second-year students at Darul HikmahIslmaic Boarding School